PENGGUNAAN KULIT MANGGIS (GARCINIA MANGOSTANA) SEBAGAI IMUNOSTIMULAN DALAM BIDANG AKUAKULTUR (ARTIKEL REVIEW) - NURI MUAHIDDAH; SEPTIANA DWIYANTI (GANEC SWARA, 2023)
Mangosteen peel contains various bioactive compounds, such as xanthones, flavonoids, and tannins, which have attracted researchers' attention as potential natural immunostimulants to enhance the immune system of fish and other aquatic organisms. In this article, various recent studies examining the effects of mangosteen peel extract on the immune response of fish and aquatic organisms have been reviewed. Some research findings include increased phagocytosis activity, survival rate, and more active total hematocrit in species such as common carp (Cyprinus carpio), Nile tilapia (Oreochromis niloticus), whiteleg shrimp (Litopenaeus vannamei), and African catfish (Clarias gariepinus) treated with mangosteen peel extract. Furthermore, administering mangosteen peel extract can promote growth in aquatic animals. In conclusion, the use of mangosteen peel extract as an immunostimulant in aquaculture holds the potential to enhance the immune response and resilience of fish and aquatic organisms. Improved immune responses can help protect them from pathogens and diseases (such as Aeromonas hydrophila and Vibrio harvey), as well as increase survival and productivity in aquaculture systems. Although these research findings are promising, further studies are needed to better understand the detailed mechanisms of action of mangosteen peel as an immunostimulant, and to evaluate optimal dosages and potential side effects. The use of mangosteen peel as an immunostimulant could serve as an effective natural alternative to strengthen the immune system of fish and aquatic organisms, but more comprehensive research is necessary before widespread and safe implementation in aquaculture practices.